Small-Molecule Lysophosphatidic Acid Receptor 5 (LPAR5) Antagonists: Versatile Pharmacological Tools to Regulate Inflammatory Signaling in BV-2 Microglia Cells - Plastira, Ioanna; Joshi, Lisha; Bernhart, Eva; Schoene, Jens; Specker, Edgar; Nazare, Marc; Sattler, Wolfgang (Frontiers in Cellular Neuroscience, 2019)
Lysophosphatidic acid (LPA) species in the extracellular environment transmit signals via six different G protein-coupled receptors (LPAR1-6). These signaling cascades are indispensible for normal brain development and function of the nervous system. However, in response to acute or chronic CNS damage LPA levels increase and aberrant signaling events can counteract brain function. Under neuroinflammatory conditions signaling along the LPA/LPAR5 axis induces a potentially neurotoxic microglia phenotype indicating the need for new pharmacological intervention strategies. Therefore we compared the effects of two novel small-molecule LPAR5 antagonists on LPA-induced polarization parameters of the BV-2 microglia cell line. AS2717638 is a selective piperidine-based LPAR5 antagonist (IC50 0.038 µM) while compound 3 is a diphenylpyrazole derivative with an IC50 concentration of 0.7 µM in BV-2 cells. At non-toxic concentrations both antagonists slightly compromised cell viability, however, at concentrations far above their IC50 concentrations. Both inhibitors blunted LPA-induced phosphorylation of STAT1 and STAT3, p65, and cJun and consequently reduced the secretion of proinflammatory cyto-/chemokines (IL-6, TNFα, IL-1β, CXCL10, CXCL2, and CCL5). Both inhibitors modulated the expression of intracellular (COX-2 and Arg1) and plasma membrane-located (CD40, CD86, and CD206) polarization markers yet only AS2717638 attenuated the neurotoxic potential of cellular supernatants collected from LPA-activated BV-2 cells towards CATH.a neurons. Our findings from the present in vitro study suggest that the two LPAR5 antagonists represent valuable pharmacological tools to interfere with LPA-induced proinflammatory signaling cascades in microglia.